On an inequality concerning a non-homogeneous Kernel and the Hypergeometric Function - He, Bing (Tamsui Oxford Journal of Mathematical Sciences)
By introducing a non-homogenous kernel of 0-degree with an independent parameter and estimating the weight function through the real function techniques, a new integral inequality with a best constant factor is established, where the best constant factor is made of both the beta function and the hypergeometric function. In addition, the reverse inequality and their corresponding equivalent forms are given.